Posted by **Chelsea** on Sunday, December 20, 2009 at 4:09pm.

(x+1)(x+2)=

(x+5)(x+6)=

(x+2)(x+7)=

(2x+3)(3x+1)=

(x+6)(x+6)=

(2x+3)(2x+3)=

(x+3) to the second power=

(x-5)to the second power=

(3x+2) to the second power=

(5x-3)to the second power=

## Answer This Question

## Related Questions

- Trig - tan(to the second power) s sin(to second power)=tan(to second power + cos...
- math115 - (-3)(-6) + (4)(-2)=10 (-3)to third power- (-8)(-2)=-43 (-6)...
- math115 - (-3)(-6) + (4)(-2)=10 (-3)to third power- (-8)(-2)=-43 (-6)...
- Algebra - I am so confused with the rules of exponents. I know them, but I have ...
- Algebra- MAT 116 - I need Help with this question: Find the value 0.2y(y to the ...
- Algebra - I'm not sure if anyone saw my question yesterday, but here it is again...
- algebra 1 - I cannot find it in my text book I have a math problem : 2f2 + 9f + ...
- math - FIND THE X INTERCEPTS OF THE GRAPH OF THE EQUATION pleaze explain thanks ...
- algebra - Hoc can the factoring of 9x to the second power plus 18x plus 8, help ...
- Basic Math - (-9) to thr second power minus (-6) to the second power: I got this...

More Related Questions